IDENTIFY ACHIEVEMENT AND LEARNING ACTIVITY OF PHYSICS PROSPECTIVE TEACHER THROUGH UTILIZATION OF WAVE-PARTICLE DUALITY TECHNOLOGY ENABLED ACTIVE LEARNING SIMULATIONS - Ahmad Swandi; Sri Rahmadhanningsih; Zose Wirawan (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Study about utilization of interactive multimedia simulation as a learning media on physics learning is very crucial. Currently, the use of interactive simulations with various learning methods has been widely used.This study aims to identify achievement and learning activity of physics teacher candidate by harnessing Technology Enabled Active Learning Simulation (TEALSim) on physics concept. The research type is Pre-Experimental with One Group Pretest-Posttest Design. The subject of the study was 41 student of physics education department at Universitas Negeri Makassar. Data analysis of this study using descriptive and quantitative analysis for research result. The results of the study revealed that there is a significant improvement on before and after giving treatment where the value of N-Gain is mayority on “enough” category by 73,09%. This indicate that the implementation of TEALSim can enhance of student’s achievement in Physics Education Department. Beside of that, according to result of student’s activity analysis, the average is above 80% that is on “very good” category which means that students are very active on doing learning of physics by the utilization of TEALSim